ANALISIS KUALITAS JARINGAN PADA LAYANAN INDIHOME UNTUK GAME ONLINE - Dove Gandaria, Aaron Gerry Ian; Sudiarta, Pande Ketut; Setiawan, Widyadi (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i01.p26, 2024)
The use and utilization of the Internet network is not only limited to its use for internet needs for social media but also for entertainment such as playing games such as the online game Valorant. The need for good network quality is very necessary to be able to play Valorant well. The purpose of this research is to determine the network quality of internet service provided by Indihome as one of the internet service providers (ISP) in Indonesia when playing the online game Valorant. With measurements using LAN cables and wireless at a speed of 50 Mbps using 2 laptop devices with the Indihome network. Measuring only the Delay and Packet Loss parameters using the Wireshark application, as well as measuring the Throughput parameters for the bandwidth requirements of the Valorant online game using the Netlimiter application for 4 weeks on Mondays and Wednesdays on weekdays and also weekends. The results of this test are the highest values of delay and packet loss for cable use, namely 6.81 ms and 0.285% and the highest values of delay and packet loss for wireless use, namely 6.15 ms and 0.548%. Where in testing the Quality of Service (QoS) value of the Indihome network when using cable and wireless, namely delay and packet loss, it shows good values compared to the TIPHON standard.